Time to Get Serious About Trialing New Scion/Rootstock Combinations - Grosser, Jude W; Gmitter, Fred G (EDIS, 2017)
It’s no secret that citrus greening disease, or HLB, continues to take a heavy toll on the beloved Florida citrus industry. It has been estimated that the industry will need to replant over 3 million trees per year for the next 10 years just to get back to normal. So the million-dollar question is “What do I plant?” What scion/rootstock combinations are available today that can justify investing in replanting? What production system will bring new trees into sustainable and profitable production? The University of Florida’s (UF) citrus breeding team thinks about these questions 24-7.